Repetitive Complete Molar Pregnancy in a 54-Year-Old Patient in a Time Distance of Eighteen Years from the First Incident: Case Report and Mini Review - Polychronis Oikonomidis; Basileios Pergialiotis; Elina Pitsouni; Stavros Natsis; Antonios Lagkadas; Konstantinos Giannakopoulos (Case Reports in Medicine)
We report a case of complete hydatidiform mole in a 54-year-old patient referred to Gynecology department of General Hospital of Athens “Laiko”, with history of previous molar pregnancy at the age of thirty-six. Our purpose was to indicate the advanced maternal age beside the long recurrence distance of the disease, which was eighteen years after the first molar pregnancy. Our diagnostic approach was through measurement of serum beta-human chorionic gonadotropin (β-HCG) and pelvic ultrasound evaluation, and the chosen therapeutic approach was abdominal hysterectomy and bilateral salpingoophorectomy.